2016
DOI: 10.1111/jcmm.12993
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages of genetically characterized familial hypercholesterolaemia patients show up‐regulation of LDL‐receptor‐related proteins

Abstract: Familial hypercholesterolaemia (FH) is a major risk for premature coronary heart disease due to severe long‐life exposure to high LDL levels. Accumulation of LDL in the vascular wall triggers atherosclerosis with activation of the innate immunity system. Here, we have investigated (i) gene expression of LDLR and LRPs in peripheral blood cells (PBLs) and in differentiated macrophages of young FH‐patients; and (ii) whether macrophage from FH patients have a differential response when exposed to high levels of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…In a previous study, we demonstrated that FH‐MAC have lower anti‐inflammatory activity and less resistance to LDL‐mediated oxidative stress, but that they retain their capacity to internalize LDL via receptors of the LDL receptor family, such as LRP5 and LRP6 (15). Here, by using quantitative real‐time PCR in FH‐MACs and non‐FH control participants (co‐MACs) of the SAFEHEART cohort, we found that miR‐505–3p expression is decreased in FH‐MACs independently of agLDL loading (FH‐MAC vs. co‐MAC: baseline, 1.33‐fold decrease, P = 0.005; lipid‐loaded cells: 1.38‐fold decrease, P = 0.002; Fig .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we demonstrated that FH‐MAC have lower anti‐inflammatory activity and less resistance to LDL‐mediated oxidative stress, but that they retain their capacity to internalize LDL via receptors of the LDL receptor family, such as LRP5 and LRP6 (15). Here, by using quantitative real‐time PCR in FH‐MACs and non‐FH control participants (co‐MACs) of the SAFEHEART cohort, we found that miR‐505–3p expression is decreased in FH‐MACs independently of agLDL loading (FH‐MAC vs. co‐MAC: baseline, 1.33‐fold decrease, P = 0.005; lipid‐loaded cells: 1.38‐fold decrease, P = 0.002; Fig .…”
Section: Resultsmentioning
confidence: 99%
“…PBMNs—obtained by using the Vacutainer CPT System (samples from the SAFEHEART cohort) or isolated from leukocyte‐rich buffy coats from heathy donors (Barcelona Blood Bank, Barcelona, Spain) by centrifugation on a Ficoll‐Hypaque gradient (GE Healthcare, Waukesha, WI, USA) (15)—were suspended in RPMI 1640 GlutaMax culture medium that was supplemented with 100 U/ml penicillin/streptomycin, 2 mM l ‐glutamine, and 10 mM Hepes buffer (Thermo Fisher Scientific, Waltham, MA, USA) and containing 10% (v/v) human serum (HS; blood group AB; Lonza, Basel, Switzerland). On the basis of the cell counts of each individual sample, PBMNs were platted on 6‐well polystyrene plates (Becton Dickinson) to obtain a cellular density of 2 × 10 6 monocytes/ml, as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations